Geometallurgical model for the exploration of mineral resources - Álvarez Castillo, Miguel Ángel (2022)
The objective of this research is to develop a geometallurgical model for mining exploration integrating geological, geochemical, and metallurgical information of an area with mining potential located in the province of Imbabura in the NW of Ecuador. The statistical processing of the geochemical dataset made up of 37 elements from 448 fluvial sediment samples was carried out by applying the compositional analysis technique with the clr and ilr log-ratio transformations using the CodaPack software, and four multi-elemental associations were defined: pathfinders of Cu-Au porphyries, Au-Ag vein pathfinders, and harmful elements in the metallurgical processes of flotation and leaching, respectively. Likewise, through the geostatistical evaluation and the estimation of the ordinary kriging, the geochemical anomaly maps were obtained for each multielemental association; Consequently, the anomalous results were spatially consistent with mapped mineral occurrences, as well as with petromineragraphic data and metallurgical recovery data from the Cascabel-Alpala porphyry Cu-Au deposits and from the La Merced de Buenos Aires Au mine. Furthermore, based on the anomalous behavior present to the SE of the four geochemical maps, a target with high prospective potential denominated "Saint Geronimo River inferred mineralization" has been defined.